The Fundamenta compositionis Jean Kuhnaus 1703. Edition, Translation, and Commentary - Frederik Kranemann; Derek Remeš (Zeitschrift der Gesellschaft für Musiktheorie)
Until now, scholars have generally doubted whether Johann Kuhnau, J. S. Bach’s predecessor as Thomaskantor in Leipzig, was indeed the author of the manuscript treatise, Fundamenta Compositionis Jean Kuhnaus 1703. Nevertheless the Fundamenta appears to originate from the Thomasschule around 1700, suggesting that it may stem from Kuhnau’s broader circle. Moreover, recent research has revealed concordances between the Fundamenta and an anonymous manuscript titled Kurtze Verfaßung (“Brief Instruction”), in addition to a number of other sources. Thus, regardless of who compiled the Fundamenta, this manuscript is significant because it reveals the pedagogical priorities, or “fundamentals” (according to the title), that often lie buried in more discursive, theoretical treatises. Therefore the ultimate value of the Fundamenta is not its originality, but rather its explication of topics such as consonance and dissonance, modes, clausulae, cadences, invertible counterpoint, and fugue in a highly condensed, practical manner with numerous musical examples. The Fundamenta is thus an excellent resource for historically informed analysis and composition at the turn of the eighteenth century, before thoroughbass accompaniment displaced vocal polyphony as the dominant pedagogical paradigm in compositional instruction. Part one of this article explores the Fundamenta’s provenance in detail; part two provides a transcription and English translation.